Representasi Perempuan dalam Iklan Produk Kecantikan di Media Sosial: Analisis Wacana Kritis Sara Mills pada Iklan Nivea Care & Protect Body Serum - Nur Aziizah Ramadani; Mahdina Dyah Purbawati; Tanaya Kirana Putri (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to analyze the representation of women in beauty product advertisements on social media, focusing on the Nivea Care & Protect Body Serum advertisement. Beauty advertisements often depict women within specific social constructions related to beauty standards, gender roles, and power relations. This research employs a qualitative descriptive approach using Sara Mills’ Critical Discourse Analysis, which emphasizes the position of subject (speaker) and object (spoken of) as well as how women are positioned in texts and visuals. Data were collected through documentation of Nivea Indonesia’s official social media posts. The results show that the advertisement not only reproduces the ideal beauty standard identified with fair and well-maintained skin but also positions women as both subjects and objects of consumption. It concludes that while there are efforts toward empowerment, the advertisement still reinforces dominant discourses that strengthen gender stereotypes in the beauty industry.